The Role Of The Head Of The Institution's Leadership In Improving The Quality Of Education At Lkp Mr. Einstein - gita noviaty (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to describe the leadership roles of the head of the institution in improving the quality of education at LKP Mr Einstein. The research focuses on four dimensions of educational leadership, namely the roles of educator, administrator, supervisor, and leader, as well as the strategic efforts undertaken by the institutional head to strengthen teacher professionalism, learning facilities, and student achievement. This study employed a descriptive qualitative approach, with data collected through in-depth interviews, direct observations, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing, supported by data validity checks through source and methodological triangulation.The findings indicate that the institutional head performs the leadership roles in an integrated and consistent manner. As an educator, the institutional head guides and facilitates teachers’ professional development through training and mentoring activities. As an administrator, the institutional head designs program plans, manages resources, and ensures the availability of a conducive learning environment. As a supervisor, the institutional head monitors the teaching process, provides constructive feedback, and addresses instructional challenges faced by teachers. As a leader, the institutional head formulates educational visions, fosters a positive organizational culture, and motivates teachers and staff through effective collaboration and communication. Furthermore, the institutional head implements strategic efforts such as enhancing teacher professionalism, improving learning facilities, and organizing student development programs including public speaking, confidence shows, and outing class activitiesIn conclusion, the effectiveness of the institutional head’s leadership significantly contributes to the improvement of educational quality at LKP Mr Einstein, particularly in the areas of instructional processes, teacher performance, and student outcomes. These findings reinforce the importance of transformational and instructional leadership within the context of non-formal education.